Family business succession: Analysis of the drivers of success based on entrepreneurship theory - Porfírio, José António (2020)
This study explores family business succession. In this study, succession is compared to the concept of opportunity versus necessity entrepreneurship. The motivations of successors when they enter the succession process are examined to identify different conditions for family business success and sustainability. The influence of context is also considered. This study is based on multilevel research and a multidisciplinary perspective. Fuzzyset qualitative comparative analysis (fsQCA) is applied to a sample of 383 observations from 6 countries (Portugal, Italy, Greece, Cyprus, North Macedonia, and Bulgaria) spanning 2 regions: southern European Mediterranean countries (Portugal, Italy, Greece, and Cyprus) and southern Slavic countries (North Macedonia and Bulgaria). The interplay between personal characteristics of the successor, organizational characteristics of the family business, and context produces different patterns that lead to different outcomes in the succession processes of family businesses. The results are important to strengthen family business theory and identify the conditions that best promote the future growth and sustainability of family businesses. The results are also important to promote country-specific public policies that may create better conditions for successors in family businesses to succeed.